A gain optical fiber based on quantum-clipped luminescent material and a preparation method thereof, and an optical fiber amplifier

CN117913635BActive Publication Date: 2026-10-16JILIN UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410089844.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-23
Publication Date
2026-10-16
Estimated Expiration
2044-01-23

AI Technical Summary

Technical Problem

[0007]本发明的创新点在于:本申请提出了用具有量子剪裁效应的发光材料制成增益光纤,解决现有增益光纤增益提升受到限制问题

Benefits of technology

[0021] First: Use luminescent materials with quantum cutting effects to make gain fibers, thus solving the problem of limited gain improvement in existing gain fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117913635B_ABST
    Figure CN117913635B_ABST
Patent Text Reader

Abstract

The application discloses a gain optical fiber based on a quantum clipping luminescent material and a preparation method and an optical fiber amplifier thereof, the gain optical fiber is a liquid-core optical fiber, and comprises a fiber core and a cladding layer covering the outside of the fiber core; the fiber core is doped with a rare earth doped perovskite luminescent material formed by combining perovskite quantum dots and rare earth ions, which can realize a quantum clipping effect, and the application proposes that the luminescent material with the quantum clipping effect is used to solve the problem that the gain improvement of the existing gain optical fiber is limited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of gain fiber technology, and in particular to a gain fiber based on quantum-cut luminescent materials, its preparation method, and an fiber amplifier. Background Technology

[0002] Due to the rapid development of all-optical networks, rare-earth ion-doped silica optical fibers are widely used as amplifying fibers in various fields requiring optical amplification and transmission. For example, the optical gain fiber disclosed in patent CN1421061A contains erbium in its core; patent CN111751925B discloses an optical fiber and its preparation method, an optical fiber amplifier, and an optical fiber laser. In this patent, the core is doped with erbium and ytterbium ions. The problem with this type of rare-earth ion-doped gain fiber is that the absorption cross-section of rare-earth ions is small, resulting in limited luminous efficiency.

[0003] The 980nm band is generally the maximum gain excitation wavelength for erbium-doped fiber amplifiers, and it plays an important role in sensors, detectors, military, and medical fields. However, gain-enhancing fibers that can achieve optical amplification in the 980nm band are limited to ytterbium-doped silica fibers. The 4f energy level diagram of ytterbium ions is characterized by a two-level system, making stimulated emission optical amplification difficult, thus hindering effective gain enhancement in ytterbium-doped fibers.

[0004] Quantum cutting refers to the physical phenomenon that for every high-energy photon absorbed by a fluorescent material, it emits two low-energy photons, with a theoretical quantum yield of 200%.

[0005] If the quantum clipping effect can be introduced into optical amplification fibers, it is expected to break through the bottleneck of existing rare-earth ion-doped fibers. Summary of the Invention

[0006] The purpose of this invention is to provide a gain optical fiber based on quantum-cut luminescent materials, its preparation method, and an optical fiber amplifier.

[0007] The innovation of this invention lies in the fact that this application proposes to use a light-emitting material with a quantum cutting effect to make a gain fiber, thereby solving the problem that the gain improvement of existing gain fibers is limited.

[0008] To achieve the above-mentioned objectives, the technical solution of this invention is as follows:

[0009] A gain fiber based on quantum-cut luminescent material, wherein the gain fiber is a liquid-core fiber, comprising a core and a cladding covering the outside of the core; characterized in that: the core is doped with a rare-earth-doped perovskite luminescent material formed by the combination of perovskite quantum dots and rare-earth ions, which can realize the quantum cutting effect.

[0010] Furthermore, for the optical amplification application at 980nm, the rare-earth-doped perovskite luminescent material is CsPbCl.x Br (3-x) :Yb 3+ Where 0 <= x <= 3; the cladding is a silica capillary; the CsPbCl x Br (3-x) :Yb 3+ The doping concentration is a quantum dot solution with an optical density OD of 10.

[0011] Furthermore, the luminescent material CsPbCl x Br (3-x) :Yb 3+ The ratio of Cl to Br is adjustable, with an optimal ratio of 9:1. The absorption peak position and Yb are controlled by adjusting the ratio of Cl to Br. 3+ The luminescence intensity of ions, Yb 3+ The doping concentration of the ions can be adjusted, with the optimal value being 5.4, by adjusting the Yb concentration. 3+ The intensity of the near-infrared emission peak of the luminescent material is controlled by the doping concentration of ions.

[0012] A method for fabricating gain optical fiber based on quantum-cut luminescent materials includes the following steps:

[0013] Step S1: Prepare the precursor cesium oleate; Add 0.814 g of cesium carbonate Cs2CO3, 30 ml of octadecene ODE and 2.5 ml of oleic acid OA solution to the reaction vessel and mix, and heat under vacuum; then heat further under inert gas protection until the precipitate is completely dissolved to form the precursor cesium oleate solution;

[0014] Step S2: Preparation of CsPbCl x Br (3-x) :Yb 3+ A quantum dot mixed solution was prepared by adding 0.086–0.286 g of ytterbium chloride hexahydrate (YbCl₃·6H₂O), 0–0.268 g of ytterbium bromide hexahydrate (YbBr₃·6H₂O), and 0.0934 g of lead acetate trihydrate (Pb(AC)₂·3H₂O) to a reaction vessel, wherein the molar mass ratio of the total molar mass of ytterbium chloride hexahydrate to that of ytterbium bromide hexahydrate to that of lead acetate trihydrate was 9:1. Then, a certain amount of methanol (MeOH), oleylamine, and octadecene were added, and the mixture was heated under vacuum to remove gases. Oleic acid was then injected, stirred until completely dissolved, and heated to obtain a mixed solution. The cesium oleate precursor solution obtained in step S1 was heated to a transparent state, and when the temperature reached 270°C, it was rapidly injected into the above mixed solution for mixing and reaction. The solution was then rapidly cooled in an ice-water mixture to obtain a solution containing CsPbCl₃·6H₂O. (3-x) :Yb 3+ A mixed solution of quantum dots;

[0015] Step S3: Preparation of CsPbCl x Br (3-x) :Yb 3+ Quantum dot solution; the CsPbCl-containing solution obtained in step S2 x Br (3-x) :Yb 3+ The quantum dot mixture was centrifuged for the first time at 7300 rpm for 10 minutes. After removing the supernatant, solvent was added to the precipitate. A second centrifugation was then performed at 10000 rpm for 6–8 minutes. The supernatant was removed again, and solvent was added to the precipitate to dissolve it. After standing, the supernatant was collected to obtain CsPbCl. x Br (3-x) :Yb 3+ Quantum dot solution;

[0016] Step S4: Prepare the fiber core solution by adding the CsPbCl obtained in step S3. x Br (3-x) :Yb 3+ The quantum dot solution dissolves in a solvent to form a fiber core solution; the CsPbCl x Br (3-x) :Yb 3+ The mixing ratio of quantum dot solution and solvent is adjusted according to the OD of the mixture to achieve an OD value of 10.

[0017] Step S5: Prepare a gain fiber based on quantum-cut luminescent material; select a hollow fiber, use pressure-assisted physical filling method to fill the core solution obtained in step S4 into the hollow fiber, then coat a small amount of fiber adhesive on the cross-section of the fiber and cure it, and after grinding and polishing, form a smooth and flat end face.

[0018] Furthermore, in steps S3 and S4, the solvent is toluene, carbon tetrachloride, chloroform, or n-hexane, with toluene being the most preferred.

[0019] An optical fiber amplifier includes at least a housing and the aforementioned gain fiber based on a quantum-cut luminescent material, wherein the gain fiber based on the quantum-cut luminescent material is disposed within the housing.

[0020] The beneficial effects of this invention are:

[0021] First: Use luminescent materials with quantum cutting effects to make gain fibers, thus solving the problem of limited gain improvement in existing gain fibers.

[0022] Secondly, in terms of material selection, perovskite quantum dots are combined with rare-earth ions to form the gain medium for amplifying optical fibers. The selected luminescent materials are perfectly matched in energy levels, achieving ultra-high quantum efficiency and gain effect. Furthermore, the gain can be adjusted by adjusting CsPbCl... xBr (3-x) The ratio of Cl to Br in perovskite can be used to adjust the absorption peak position and Yb 3+ The luminescence intensity of the ions; due to the small size of quantum dots, the scattering of light is almost negligible, thus CsPbCl x Br (3-x) :Yb 3+ Liquid-core optical fibers do not exhibit significant scattering loss. Under excitation by excitation light, CsPbCl... x Br (3-x) :Yb 3+ After excitation, the particles are first excited to the conduction band of the perovskite matrix, and some electrons relax to the Yb group. 3+ The ion energy level is twice the corresponding energy level, and then two electrons are pumped into Yb. 3+ 2F of ions 5 / 2 state, and radiate to Yb 3+ 2F of ions 7 / 2 In this state, a single photon from the perovskite host can excite Yb 3+ The generation of two photons enables quantum clipping, achieving a photoluminescence quantum yield close to 170%, and constitutes a three-level structure, facilitating population inversion. CsPbCl x Br (3-x) :Yb 3+ It possesses narrowband luminescence with rare earth ions, long energy level lifetime, easy population inversion optical amplification, and also exhibits CsPbCl... x Br (3-x) The large absorption cross-section of perovskite quantum dots solves the problems of limited gain and high threshold in rare-earth ion-doped optical fibers. Furthermore, the gain can be further improved by adjusting the Cl / Br ratio and Yb... 3+ The amplification capability of optical fibers can be controlled by adjusting the doping concentration of ions. Attached Figure Description

[0023] Figure 1 Based on CsPbCl x Br (3-x) :Yb 3+ Schematic diagram of quantum dot-doped liquid core gain fiber structure.

[0024] Figure 2 It is CsPbCl x Br (3-x) :Yb 3+ Illustration of quantum dot-doped liquid core gain fiber filling.

[0025] Figure 3 It is CsPbCl x Br (3-x) :Yb 3+ Excitation spectrum of quantum dots.

[0026] Figure 4 It is CsPbCl x Br (3-x) :Yb 3+ Photoluminescence spectroscopy (PL) of quantum dot-doped liquid core-gain fiber output.

[0027] Figure 5 It is four proportions of CsPbCl x Br (3-x) :Yb 3+ Experimental curves showing the relationship between output light intensity and pump power in quantum dot-doped liquid-core gain optical fiber.

[0028] Figure 6 It is CsPbCl x Br (3-x) :Yb 3+ Experimental curves showing the relationship between the output light intensity of a quantum dot-doped liquid-core gain fiber and the quantum dot concentration and fiber length.

[0029] Figure 7 It is CsPbCl x Br (3-x) :Yb 3+ Schematic diagram of a quantum dot-doped liquid-core gain fiber amplifier.

[0030] Figure 8 It is CsPbCl x Br (3-x) :Yb 3+ Quantum doped liquid core gain fiber optical amplification performance gain diagram.

[0031] In the diagram: 1 is the fiber core, 2 is the cladding, 3 is the UV adhesive, and 4 is the syringe. Detailed Implementation

[0032] The technical solutions in the embodiments of the present invention will now be clearly and completely described in conjunction with the accompanying drawings.

[0033] Example 1:

[0034] 1. To prepare the precursor cesium oleate solution, Cs2CO3 (0.814 g, 2.5 mmol), 30 mL ODE and 2.5 mL OA were placed in a 100 mL three-necked flask and heated under vacuum to 120 °C for 1 hour. The mixture was then further heated to 150 °C under N2 for 3 hours until the precipitate was completely dissolved, thus obtaining the precursor cesium oleate solution.

[0035] 2. Preparation of CsPbCl x Br (3-x) :Yb 3+Quantum dot mixed solution: Add 4 ml of oleylamine (OLA) and 20 ml of octadecene (ODE) to a three-necked flask, then add 0.286 g of ytterbium chloride hexahydrate (YbCl3·6H2O, 99.9% metal-based) and 0.0934 g of lead acetate trihydrate (Pb(AC)2·3H2O, 99.99% metal-based), followed by 1 ml of methanol (MeOH, 99%). Place the three-necked flask under vacuum and heat to 120°C to remove gases for 1 hour. Then, 4 ml of oleic acid (OA) was injected into a three-necked flask to prevent rapid oxidation of OA upon contact with oxygen. The mixture was stirred until completely dissolved, yielding a mixture. The mixture was heated to 270°C. 1.6 ml of the precursor cesium oleate solution was drawn into a syringe and heated to a transparent state using a hairdryer. At 270°C, this solution was rapidly injected into the above mixed solution. After reacting for 8 seconds, the solution was placed in an ice-water mixture to rapidly cool it to below 50°C, yielding a solution containing CsPbCl. x Br (3-x) :Yb 3+ A mixed solution of quantum dots.

[0036] 3. Preparation of CsPbCl x Br (3-x) :Yb 3+ Quantum dot solution: The prepared CsPbCl x Br (3-x) :Yb 3+ The mixed solution was drawn into four 10ml centrifuge tubes and centrifuged at 7300 rpm for 8–10 minutes. The supernatant was discarded, and 2ml of toluene was added to the precipitate to dissolve it. A second centrifugation was performed at 10000 rpm for 8–10 minutes. The supernatant was discarded again, and 0.5–1ml of toluene was added to the tubes to dissolve the precipitate. The mixture was allowed to stand for at least 6 hours, and the supernatant was collected to obtain the desired CsPbCl₂. x Br (3-x) :Yb 3+ Quantum dot solution.

[0037] 4. Fabrication of optical fibers

[0038] The structure of gain fiber based on quantum-tailored luminescent materials is as follows: Figure 1 As shown, core 1 is a light-emitting material-doped core with quantum cutting effect, wherein the dopant is CsPbCl. x Br (3-x) :Yb 3+ The quantum dot cladding 2 is composed of SiO2 material with a lower refractive index than the core 1.

[0039] Preparation of CsPbCl x Br (3-x) :Yb 3+Quantum doped fiber, using 100 / 125μm hollow fiber, CsPbCl was added using a pressure-assisted physical filling method. x Br (3-x) :Yb 3+ Quantum dot solution was poured into 100 / 125μm hollow optical fiber.

[0040] like Figure 2 As shown, CsPbCl x Br (3-x) :Yb 3+ The quantum dot solution is placed in a container, and one end of the hollow optical fiber extends into CsPbCl. x Br (3-x) :Yb 3+ In the quantum dot solution, the other end is connected to syringe 4 via UV gel 3, and syringe 4 is used to draw CsPbCl from the container. x Br (3-x) :Yb 3+ Quantum dot solution is used to fill optical fibers. After completion, a small amount of fiber adhesive is applied to the cross-section of the optical fiber and cured. After grinding and polishing, a smooth and flat end face is formed.

[0041] Example 2

[0042] 1. Prepare the precursor cesium oleate solution using the same method as in Example 1.

[0043] 2. Preparation of CsPbCl x Br (3-x) :Yb 3+ Quantum dot mixed solution: 0.256 g of ytterbium chloride hexahydrate (YbCl3·6H2O, 99.9% metal-based), 0.038 g of ytterbium bromide hexahydrate (YbBr3·6H2O, 99.9% metal-based) and 0.0934 g of lead acetate trihydrate (Pb(AC)2·3H2O, 99.99% metal-based) were added to a three-necked flask, and the remaining synthesis steps were the same as in Example 1.

[0044] 3. Preparation of CsPbCl x Br (3-x) :Yb 3+ Quantum dot solution: The method is the same as in Example 1.

[0045] 4. Fabrication of optical fiber: The method is the same as in Example 1.

[0046] Example 3

[0047] 1. Prepare the precursor cesium oleate solution using the same method as in Example 1.

[0048] 2. Preparation of CsPbCl x Br (3-x) :Yb3+ Quantum dot mixed solution: 0.228 g of ytterbium chloride hexahydrate (YbCl3·6H2O, 99.9% metal-based), 0.076 g of ytterbium bromide hexahydrate (YbBr3·6H2O, 99.9% metal-based) and 0.0934 g of lead acetate trihydrate (Pb(AC)2·3H2O, 99.99% metal-based) were added to a three-necked flask, and the remaining synthesis steps were the same as in Example 1.

[0049] 3. Preparation of CsPbCl x Br (3-x) :Yb 3+ Quantum dot solution: The method is the same as in Example 1.

[0050] 4. Prepare optical fibers using the same method as in Example 1.

[0051] Example 4

[0052] 1. Prepare the precursor cesium oleate solution using the same method as in Example 1.

[0053] 2. Preparation of CsPbCl x Br (3-x) :Yb 3+ Quantum dot mixed solution: 0.198 g of ytterbium chloride hexahydrate (YbCl3·6H2O, 99.9% metal-based), 0.114 g of ytterbium bromide hexahydrate (YbBr3·6H2O, 99.9% metal-based) and 0.0934 g of lead acetate trihydrate (Pb(AC)2·3H2O, 99.99% metal-based) were added to a three-necked flask, and the remaining synthesis steps were the same as in Example 1.

[0054] 3. Preparation of CsPbCl x Br (3-x) :Yb 3+ Quantum dot solution: The method is the same as in Example 1.

[0055] 4. Prepare optical fibers using the same method as in Example 1.

[0056] Example 5

[0057] 1. Prepare the precursor cesium oleate solution using the same method as in Example 1.

[0058] 2. Preparation of CsPbCl x Br (3-x) :Yb 3+Quantum dot mixed solution: 0.172 g of ytterbium chloride hexahydrate (YbCl3·6H2O, 99.9% metal-based), 0.152 g of ytterbium bromide hexahydrate (YbBr3·6H2O, 99.9% metal-based) and 0.0934 g of lead acetate trihydrate (Pb(AC)2·3H2O, 99.99% metal-based) were added to a three-necked flask, and the remaining synthesis steps were the same as in Example 1.

[0059] 3. Preparation of CsPbCl x Br (3-x) :Yb 3+ Quantum dot solution: The method is the same as in Example 1.

[0060] 4. Prepare optical fibers using the same method as in Example 1.

[0061] The output gain results of the optical fibers prepared in Examples 1-5 were compared. The test methods were all performed by using a 20.11mW 405nm laser as the pump source for excitation. The test results are shown in Table 1.

[0062] Table 1

[0063]

[0064] Table 1 shows that the quantum dot material with a Cl / Br ratio of 9:1 exhibits the strongest luminescence intensity at 980 nm, the same as that of ytterbium ions, among the five doping ratios. Furthermore, beyond the 9:1 ratio, the luminescence intensity in the near-infrared region decreases with decreasing chlorine ratio. Therefore, in fiber optic amplifier applications, quantum dots with a Cl / Br ratio of 9:1 are selected as the doping material. Their excitation spectra were tested, and the results are as follows... Figure 3 The excitation spectrum shown is used to determine CsPbCl x Br (3-x) :Yb 3+ A 405nm laser can be used as the pump source for quantum dot-doped fiber amplifiers.

[0065] After the optical fiber was fabricated, the output photoluminescence spectrum of the optical fiber was tested, and the results were as follows: Figure 4 The PL spectrum shown demonstrates that this fiber achieves light output in both the visible and infrared regions. The output power of the amplified fiber is related to the pump power and CsPbCl... x Br (3-x) :Yb 3+ The OD value of quantum dot solutions is related to the length of optical fibers.

[0066] Figure 5 The CsPbCl prepared in the first four examples was selected. x Br (3-x) :Yb 3+The experimental relationship between the output power of quantum dot-doped amplification fiber and the pump light power shows that the output intensity of the fiber is strongest when the Cl / Br ratio is 9:1, and both increase with the increase of pump power.

[0067] Figure 6 It is CsPbCl x Br (3-x) :Yb 3+ The effects of the OD value of the quantum dot solution and the length of the doped fiber on the output power of the fiber were investigated. A 405nm laser was selected as the pump source, and the fiber was cut to the required length using a fiber shearing tool. A small amount of fiber adhesive was applied and cured, and then ground and polished to form a smooth and flat end face for easy experimental testing. The experiment showed that the output intensity of the fiber is related to both the fiber length and the OD value of the solution. The experiment found that under the same pump laser power excitation, the optimal fiber length was 11cm and the optimal OD value was 10.

[0068] Example 6

[0069] refer to Figure 7 A fiber amplifier based on a gain fiber of a quantum-cut luminescent material includes a housing (not shown in the figure) and a CsPbCl disposed within the housing. x Br (3-x) :Yb 3+ The quantum dot-doped amplifying fiber uses a 405nm laser as the pump source for the fiber amplifier section, and a broadband light source covering 980-1100nm is selected as the signal source. The signal light and pump light are connected to CsPbCl via a wavelength division multiplexer. x Br (3-x) :Yb 3+ On the quantum dot-doped amplification fiber, the quantum dots are dissolved in a toluene (C7H8, 99.5%) solution, and the other end of the fiber is connected to a fiber optic spectrometer to detect the amplified spectrum.

[0070] Example 7

[0071] A fiber amplifier based on a gain fiber of a quantum-cut luminescent material includes a housing (not shown) and a CsPbCl disposed within the housing. x Br (3-x) :Yb 3+ The quantum dot-doped amplifying fiber uses a 405nm laser as the pump source for the fiber amplifier section, and a broadband light source covering 980-1100nm is selected as the signal source. The signal light and pump light are connected to CsPbCl via a wavelength division multiplexer. x Br (3-x) :Yb 3+On a quantum dot-doped amplification fiber, quantum dots are dissolved in a hexane (CH3(CH2)4CH3, 99.5%) solution, and the other end of the fiber is connected to a fiber optic spectrometer to detect the amplified spectrum.

[0072] Example 8

[0073] A fiber amplifier based on a gain fiber of a quantum-cut luminescent material includes a housing (not shown) and a CsPbCl disposed within the housing. x Br (3-x) :Yb 3+ The quantum dot-doped amplifying fiber uses a 405nm laser as the pump source for the fiber amplifier section, and a broadband light source covering 980-1100nm is selected as the signal source. The signal light and pump light are connected to CsPbCl via a wavelength division multiplexer. x Br (3-x) :Yb 3+ The quantum dot-doped amplification fiber uses a chloroform (CHCl3, 99.5%) solution to dissolve the quantum dots, and the other end of the fiber is connected to a fiber optic spectrometer to detect the amplified spectrum.

[0074] Example 9

[0075] A fiber amplifier based on a gain fiber of a quantum-cut luminescent material includes a housing (not shown) and a CsPbCl disposed within the housing. x Br (3-x) :Yb 3+ The quantum dot-doped amplifying fiber uses a 405nm laser as the pump source for the fiber amplifier section, and a broadband light source covering 980-1100nm is selected as the signal source. The signal light and pump light are connected to CsPbCl via a wavelength division multiplexer. x Br (3-x) :Yb 3+ On the quantum dot-doped amplification fiber, the quantum dots are dissolved in a carbon tetrachloride (CCl4, 99.9%) solution, and the other end of the fiber is connected to a fiber optic spectrometer to detect the amplified spectrum.

[0076] To ensure the stability of the light source during testing, both light sources were first turned on for preheating. Then, the 405nm laser was turned off, and the output spectrum was measured when only the signal light was input. The gain was measured with the pump source being a 405nm laser, the pump power being 20.11mW, and the signal light being -30dB. The test results are shown in Table 2.

[0077] Table 2

[0078] 6 1.49 0.824 25 7 1.375 0.896 12 8 1.59 0.725 17 9 1.505 1 21

[0079] Choosing toluene as the solvent from Table 2 results in the highest gain for the fiber amplifier. This is mainly because the refractive index of toluene solution is closest to that of the cladding SiO2 silicon dioxide (1.45), and it can make the core refractive index greater than the cladding refractive index, thereby achieving total internal reflection of the fiber and achieving the best optical amplification effect.

[0080] Then, the pump light is turned on, and by adjusting different pump intensities, the spectra obtained when the pump light and signal light are input together are recorded using a spectrometer, thus obtaining CsPbCl. x Br (3-x) :Yb 3+ Gain profile of a quantum dot-doped fiber amplifier, such as Figure 8 As shown.

[0081] Compared with existing ytterbium-doped fiber amplifiers, the fiber amplifier in this example has the following advantages:

[0082] Perovskite quantum dots are known to have a very large absorption cross section (10). -16 (on the order of magnitude), while most rare earth ions, taking ytterbium ions as an example, are on the order of 10. -21 Furthermore, it possesses a long energy level lifetime, in addition to CsPbCl x Br (3-x) :Yb 3+ It can also realize the quantum cutting effect, introducing quantum-cut luminescent materials into gain fibers and fiber amplifiers, achieving higher gain values, reaching >29dB, which exceeds the gain index of traditional ytterbium ion-doped fiber amplifiers.

[0083] The described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A gain fiber based on quantum-cut luminescent materials, wherein the gain fiber is a liquid-core fiber, comprising a core and a cladding covering the outside of the core; characterized in that: The fiber core is doped with a rare-earth-doped perovskite luminescent material formed by the combination of perovskite quantum dots and rare-earth ions, which enables quantum tailoring effects; for light amplification at 980nm, the rare-earth-doped perovskite luminescent material is CsPbCl. x Br (3-x) :Yb 3+ Where 0 <= x <= 3; the cladding is a silica capillary; the CsPbCl x Br (3-x) :Yb 3+ The doping concentration is a quantum dot solution with an optical density OD of 10, and the luminescent material CsPbCl x Br (3-x) :Yb 3+ The ratio of Cl to Br is adjustable; by adjusting the ratio of Cl to Br, the absorption peak position and Yb can be controlled. 3+ The luminescence intensity of ions; Yb 3+ The doping concentration of the ions can be adjusted by adjusting the Yb 3+ The intensity of the near-infrared emission peak of the luminescent material is controlled by the doping concentration of ions.

2. The gain optical fiber based on quantum-tailored luminescent materials according to claim 1, characterized in that: The luminescent material CsPbCl x Br (3-x) :Yb 3+ The ratio of Cl to Br in Yb is 9:

1. 3+ The ion doping concentration is 5.

4.

3. A method for fabricating a gain optical fiber based on quantum-tailored luminescent materials as described in any one of claims 1-2, characterized in that: Includes the following steps: Step S1: Prepare the precursor cesium oleate; 0.814 g of cesium carbonate (Cs₂CO₃), 30 ml of octadecene ODE, and 2.5 ml of oleic acid (OA) solution were added to a reaction vessel and mixed. The mixture was heated under vacuum. Then, it was heated further under an inert gas atmosphere until the precipitate was completely dissolved, forming a cesium oleate precursor solution. Step S2: Preparation of CsPbCl x Br (3-x) :Yb 3+ A quantum dot mixed solution was prepared by adding 0.086–0.286 g of ytterbium chloride hexahydrate (YbCl₃·6H₂O), 0–0.268 g of ytterbium bromide hexahydrate (YbBr₃·6H₂O), and 0.0934 g of lead acetate trihydrate (Pb(AC)₂·3H₂O) to a reaction vessel, wherein the molar mass ratio of the total molar mass of ytterbium chloride hexahydrate to that of ytterbium bromide hexahydrate to that of lead acetate trihydrate was 9:

1. Then, a certain amount of methanol (MeOH), oleylamine, and octadecene were added, and the mixture was heated under vacuum to remove gases. Oleic acid was then injected, stirred until completely dissolved, and heated to obtain a mixed solution. The cesium oleate precursor solution obtained in step S1 was heated to a transparent state, and when the temperature reached 270°C, it was rapidly injected into the above mixed solution for mixing and reaction. The solution was then rapidly cooled in an ice-water mixture to obtain a solution containing CsPbCl₃·6H₂O. (3-x) :Yb 3+ A mixed solution of quantum dots; Step S3: Preparation of CsPbCl x Br (3-x) :Yb 3+ Quantum dot solution; the CsPbCl-containing solution obtained in step S2 x Br (3-x) :Yb 3+ The quantum dot mixture was centrifuged for the first time at 7300 rpm for 10 minutes. After removing the supernatant, solvent was added to the precipitate. A second centrifugation was then performed at 10000 rpm for 8-10 minutes. The supernatant was removed again, and solvent was added to the precipitate to dissolve it. After standing, the supernatant was collected to obtain CsPbCl. x Br (3-x) :Yb 3+ Quantum dot solution; Step S4: Prepare the fiber core solution; use the CsPbCl obtained in step S3. x Br (3-x) :Yb 3+ The quantum dot solution dissolves in a solvent to form a fiber core solution; the CsPbCl x Br (3-x) :Yb 3+ The mixing ratio of quantum dot solution and solvent is adjusted according to the OD of the mixture to achieve an OD value of 10. Step S5: Prepare a gain fiber based on quantum-cut luminescent material; select a hollow fiber, use pressure-assisted physical filling method to fill the core solution obtained in step S4 into the hollow fiber, then coat a small amount of fiber adhesive on the cross-section of the fiber and cure it, and after grinding and polishing, form a smooth and flat end face.

4. The method for fabricating a gain optical fiber based on quantum-tailored luminescent materials according to claim 3, characterized in that: In steps S3 and S4, the solvent is toluene, carbon tetrachloride, chloroform, or n-hexane.

5. An optical fiber amplifier, characterized in that: It includes at least a housing and a gain optical fiber based on quantum-cut luminescent material as described in any one of claims 1-2, wherein the gain optical fiber based on quantum-cut luminescent material is disposed within the housing.

Citation Information

Patent Citations

  • Optical fibers and their fabrication methods, optical fiber amplifiers, and fiber lasers.

    CN111751925B

  • Optical gain fibers

    CN1421061A

  • Manufacturing method and temperature detection method for PbSe quantum dot liquid-core optical fiber temperature sensor

    CN104165706A

  • Solar light condensation plate based on quantum cutting effect

    CN111170646A